Pengaruh Inovasi Produk, Label Halal Dan Label Bpom Terhadap Minat Beli Kosmetik Maybelline (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Khusnul Khotimah; Budi Wahono; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the effect of product innovation, halal labels and BPOM labels on the interest in buying Maybelline Cosmetics for FEB Students at the Islamic University of Malang. The sample used in this study was 90 respondents using a purposive sampling technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and partial hypothesis (Test t). The results of this study indicate that the variable product innovation, the halal label and the BPOM label have a significant effect on the intention to buy Maybelline cosmetics simultaneously or partially. Keywords: Product Innovation, Halal Label, BPOM Label, Buying Interest